Strengthening the Legal Protection of Waqf Assets through Participatory Assistance: A Community-Based Waqf Deed Facilitation Program in Kemirian Village, Indonesia - Halili; Siti Andini; Hafideh; Maulidiah; Elok Ayu Nandari; Maulidya Hasanah; Lailatus Sa’diah; Tasya Aulia Arsul Masfufah; Putri Elitya; Putri Melinda; Faesiyatul Lailiyah; Rofidatus Saniah; Saini (BAMALA Institute, 2026)
Waqf assets play an important role in sustaining religious, educational, and social activities in rural communities. However, many waqf assets remain vulnerable because their legal status has not been formally documented through a Waqf Pledge Deed (Akta Ikrar Wakaf or AIW). This community service program aimed to strengthen the legal protection of waqf assets in Kemirian Village, Indonesia, by improving community legal literacy and facilitating the administrative formalization of waqf assets. The program employed a participatory assistance approach that integrated legal education, waqf asset identification, document inventory, administrative verification, social mediation, and facilitation with the Waqf Pledge Deed Official (PPAIW) at the local Office of Religious Affairs (KUA). The implementation revealed several barriers to waqf legalization, including incomplete historical ownership documents, limited administrative capacity among nazhir, operational constraints, and concerns regarding potential social tensions with heirs. Through intensive assistance, community administrators were supported in organizing required documents, understanding legal procedures, communicating with relevant institutions, and advancing the waqf pledge process. One identified prayer-room asset successfully progressed through a critical stage of waqf legalization, providing a practical reference for other community-managed religious assets. The program demonstrates that participatory assistance can bridge the gap between religious recognition and formal legal certainty. It also highlights the strategic role of higher education institutions in strengthening nazhir capacity, facilitating institutional coordination, and supporting sustainable community-based waqf governance.